Prognostic significance and optimal candidates of primary tumor resection in major salivary gland carcinoma patients with distant metastases at initial presentation: A population-based study. (March 2018) - Shi, Xiao; Dong, Fan; Wei, Wenjun; Song, Kehan; Huang, Naisi; Lu, Zhongwu; Lei, Bowen; Yu, Pengcheng; Liu, Wanlin; Wang, Yu; Sun, Guohua; Wang, Yulong; et al.
Highlights: Our study firstly confirmed the prognostic benefit of PTR on M1 MaSGC patients. Our research firstly identified optimal candidates for PTR. Our study firstly revealed distribution of metastatic sites at diagnosis in MaSGC. Abstract: Objectives: To investigate the prognostic significance and identify optimal candidates of primary tumor resection (PTR) for patients with metastatic major salivary gland carcinoma (MaSGC) at diagnosis. Materials and methods: Patients with metastatic MaSGC were identified from the Surveillance, Epidemiology and End Results (SEER) database. Kaplan-Meier analyses, log-rank tests and multivariate Cox regression models were employed to evaluate the therapeutic roles of PTR in the overall cohort and different subgroups. Results: Overall, 255 patients were included in our study, among whom 80 (31.4%) received PTR. PTR was associated with decreased overall mortality (OM) and cancer-specific mortality (CSM) in the overall cohort (PTR vs No-PTR, HR: 0.363, 95%CI: 0.204–0.646, p = .001 for OM; HR: 0.439, 95%CI: 0.243–0.794, p = .006 for CSM). When we focused on site-specific metastases, receipt of PTR significantly reduced the risk of OM for patients with lung, bone or distant lymph node involvement (all p < .05), whereas this surgical procedure not only failed to bring survival benefit, but even seemed to insignificantly increase the mortality risk once liver metastases were presented (PTR vs No-PTR, HR: 1.109, 95%CI: 0.279–4.412 for OM; HR: 1.596, 95%CI: 0.364–7.004 for CSM). In addition, subgroup analyses showed that patients with stage T1-3 disease, younger age (<65), single-site metastases and high-risk pathologies might benefit from PTR. Conclusion: Our study for the first time verifies the favorable prognostic impact of PTR for highly-selected patients with metastatic MaSGC at diagnosis and has the potential to be adopted in future clinical practice, although long-term prospective studies are warranted.